Training on the Implementation of the Strengthening Student Profile Project of Pancasila PKM at SMK Negeri 7 Takalar - Baso, Fadhlirrahman; Hidayat M, Wahyu; Ashadi, Ninik Rahayu; Setialaksana, Wirawan; Fadhilatunisa, Della (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2024)
This article discusses a community service program which aims to strengthen the profile of Pancasila among Vocational High School (SMK) students, especially at SMK Negeri 7 Takalar. This program is designed to increase teacher capacity in integrating Pancasila values ​​into learning. The methods used are lectures, group discussions, and direct practice in making P5 projects. Follow-up steps include the formation of a monitoring group, integration of Pancasila values ​​in the curriculum, development of follow-up programs, collaboration with parents and the community, involvement of teachers and school staff, and regular evaluations. The program results show the program is effective in improving teachers' understanding of P5 concepts and their skills in designing projects. However, further support is still needed in terms of resources and time for optimal implementation of P5 in schools. This article provides guidance for the development of similar programs in vocational education institutions. Regular evaluation and feedback is implemented to ensure the sustainability and expansion of the impact of this program in shaping student character based on Pancasila values.